Some questions of ethics and ethics in the practice of the medical examiner - Белецкая, А. А. (Theory and practice of jurisprudence, 2016)
The article focuses on some issues of medical ethics and deontology in the practice of the medical examiner during the examination of a living person and a dead body. Expert opinion may be evidence in criminal and civil cases and has important implications that imposes on him the highest professional and ethical responsibility.